DEVELOPMENT OF PROSPECTIVE TEACHERS LEARNING MODEL INTEGRATING ICT CYBERWELLNESS IN THE CONCEPT OF CONTINUOUS, CONVERGENT AND CONCENTRIC - Kuswandi, Dedi; Adi, Eka Pramono; Soepriyanto, Yerry (2015)
Educating prospective teachers in the use of information and communication technology (ICT) has to improve/enhance teaching-learning process, and it has the commitment and becomes an important goal in all educational programs at State University of Malang. The era of innovative learning and ICT-based have changed the way teachers and students' interact, and now teaches the method of one-way, unable to provide maximum learning outcomes for student learning. Development of prospective teachers' learning model in terms integrates ICT cyberwellness with the concept of continuous, convergent and concentric (as culture integration concept from Ki Hadjar Dewantara) web-based open source platform on student teachers has been made possible to a limited circle. Learning and the design of interconnection systems design has been carried out based on the stage of development. keywords: cyberwellness, prospective teacher, continuous, convergent, concentric